Germany : Financial Sector Assessment Program-Anti-Money Laundering and Combating the Financing of Terrorism-Technical Notes. (IMF Staff Country Reports; Country Report ;, 2016)
This paper sets out the findings and recommendations in the selected areas of Germany's Anti- Money Laundering and Combating the Financing of Terrorism (AML/CFT) regime made in the context of the Financial Sector Assessment Program. It summarizes the findings of a targeted review of Germany's money laundering offense, measures to ensure the transparency of legal persons, and the implementation of AML/CFT measures by banks with cross-border operations. According to the 2010 Mutual Evaluation Report, Germany is vulnerable to ML and FT for following reasons: its strategic location in Europe and large economy, open financial center, open borders, and strong international linkages.